Genomic Analysis of the Olfactory Receptor Region of the Mouse and Human T-Cell Receptor α/δ Loci - Lane, Robert P.; Roach, Jared C.; Lee, Inyoul Y.; Boysen, Cecilie; Smit, Arian; Trask, Barbara J.; Hood, Leroy (Genome Research, 2002)
We have conducted a comparative genomic analysis of several olfactory receptor (OR) genes that lie immediately 5′ to the V-α gene segments at the mouse and human T-cell receptor (TCR) α/δ loci. Five OR genes are identified in the human cluster. The murine cluster has at least six OR genes; the first five are orthologous to the human genes. The sixth mouse gene has arisen since mouse-human divergence by a duplication of a ∼10-kb block. One pair of OR paralogs found at the mouse and human loci are more similar to each other than to their corresponding orthologs. This paralogous “twinning” appears to be under selection, perhaps to increase sensitivity to particular odorants or to resolve structurally-similar odorants. The promoter regions of the mouse OR genes were identified by RACE-PCR. Orthologs share extensive 5′ UTR homology, but we find no significant similarity among paralogs. These findings extend previous observations that suggest that OR genes do not share local significant regulatory homology despite having a common regulatory agenda. We also identified a diverged TCR-α gene segment that uses a divergent recombination signal sequence (RSS) to initiate recombination in T-cells from within the OR region. We explored the hypothesis that OR genes may use DNA recombination in expressing neurons, e.g., to recombine ORs into a transcriptionally active locus. We searched the mouse sequence for OR-flanking RSS motifs, but did not find evidence to suggest that these OR genes use TCR-like recombination target sequences.